2000
DOI: 10.1001/archneur.57.4.489
|View full text |Cite
|
Sign up to set email alerts
|

Visuoperceptual Impairment in Dementia With Lewy Bodies

Abstract: Visual perception is defective in probable DLB. The defective visual perception plays a role in development of visual hallucinations, delusional misidentifications, visual agnosias, and visuoconstructive disability charcteristic of DLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
2
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(120 citation statements)
references
References 33 publications
7
109
2
2
Order By: Relevance
“…In the present study, hallucinating DLB/ PDD patients were more impaired in all visual scores compared to patients without hallucinations. The interpretation of this finding needs caution, because as in previous studies, 39,40 the number of demented patients without hallucinations in this study was small (n ϭ 8).…”
Section: Figure (A Through C) Mean and 95% CI Of The Discrimination contrasting
confidence: 49%
See 1 more Smart Citation
“…In the present study, hallucinating DLB/ PDD patients were more impaired in all visual scores compared to patients without hallucinations. The interpretation of this finding needs caution, because as in previous studies, 39,40 the number of demented patients without hallucinations in this study was small (n ϭ 8).…”
Section: Figure (A Through C) Mean and 95% CI Of The Discrimination contrasting
confidence: 49%
“…Visual impairments in DLB patients with visual hallucination exceed those without hallucination, especially in the overlapping figure task 39 and in the line orientation task. 40 Barnes and David 41 compared visual imagery, visual perception, and recognition memory in nondemented PD patients with and without hallucinations and found that PD patients with visual hallucinations were more impaired in object perception.…”
Section: Figure (A Through C) Mean and 95% CI Of The Discrimination mentioning
confidence: 87%
“…A much more severe impairment in copying tasks is observed in early-onset AD patients and in PCA variant, in which severe constructive defects are usually associated with progressive visual-spatial disorders, including Balint syndrome and unilateral spatial neglect [100,101]. A very similar pattern of drawing impairment is found in LBD, in which visuospatial difficulties are often early and prominent and contribute to the disproportionate impairment in constructional tasks observed in these patients [151][152][153].…”
Section: Discussionmentioning
confidence: 91%
“…Visuospatial tasks, such as object size discrimination, form discrimination, overlapping figure identification, and visual counting tasks, may reveal more impaired performances in LBD than in AD, and these defects likely contribute to the disproportionate impairment in constructional tasks in LBD patients [151][152][153].…”
Section: Drawing Disorders In Lewy Body Dementiamentioning
confidence: 99%
“…150 Individuals with DLB (n = 24) had a poorer performance than those with AD (n = 48) on object size discrimination, form discrimination, overlapping figure identification, and on visual counting tasks. 151 This was concluded to play a role in the perceptual deficits observed in DLB, such as visual hallucinations. Other complex visual tasks such as colour integration and rotated object comparison are also impaired in DLB, which corresponds with the cortical areas affected by the disease.…”
Section: Complex Visual Functionsmentioning
confidence: 99%